Food Activism and Citizens’ Democratic Engagements: What Can We Learn from Market-Based Political Participation? - Lorenzini, Jasmine (2019)
Food democracy calls for a democratization of the production, distribution, and consumption of food. Researchers and lay citizens are showing a growing interest for initiatives associated with food democracy, yet the specific democratic ideals and involvements that make up food democracy have gained limited attention. Many forms of participation associated with food democracy are market-based, such as buying organic food or joining community-supported agricultural projects. Research shows that market-based logics influence multiple spheres of life and threaten democratic ideals. However, scholars working on political participation have not yet analyzed the influence of market-based logics across forms of participation. This article analyses the action repertoire of food democracy to assess the influence of market-based logics on different forms of food activism. It builds on four critiques of market-based politics to question the relationship between different forms of participation and the market. It addresses three research questions: Which forms of political participation do citizens use to democratize the food regime? Which conceptions of democracy relate to these different forms of food activism? Which critiques of market-based politics apply to different forms of food activism? The article highlights the widespread risk of unequal participation, crowding out, commodification, and state retreat across forms of participation used to democratize food regimes. This study provides insights into the types of democratic renewal being experimented with in the framework of food democracy as well as their limits.